Cross-Cultural Learning and Adaptation: Enhancing Madrasah Management in Afghanistan through Insights from Indonesian Madrasah - Rizapoor, Habiburrahman; Zafari, Mohammad Anwar (IAIN Ponorogo, 2024)
This article explores the potential for applying Indonesian Madrasah management practices to improve Madrasah institutions in Afghanistan. Madrasahs are crucial for Afghan religious education and social cohesion but need help in implementing modern management principles. Using a comparative approach, the study examines key management strategies in Indonesian Madrasahs, known for their strong Islamic educational tradition and modern management foundations. The research aims to identify adaptable strategies for Afghan Madrasahs, with two main goals: not only understanding current Afghan practices to pinpoint challenges and areas for improvement but also providing evidence-based recommendations from Indonesian models. The study acknowledges the cultural and social differences between Afghanistan and Indonesia, emphasizing the need for contextual adaptation of management strategies. The significance of this research lies in its potential to enhance Madrasah education in Afghanistan, contributing to human resource development, community building, and societal progress. It also aims to foster intercultural exchange and collaboration between Afghanistan and Indonesia in Islamic education management. By integrating successful Indonesian management techniques, the study aspires to offer practical solutions to optimize educational outcomes and organizational efficiency in Afghan Madrasahs.